KOMODIFIKASI TELETABLOID JATANRAS DI TELEVISI ‘’NET’’ - DEDE ROHALI; RENI OKTARI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Share and rating is like a ’fate’ that must be fought by the mainstream media to stay alive, even including NET which previously intended to be one alternative to watching a screen. If in the past NET still avoided crime content or things that smelled of crime and violence, then at this time crime content has become one of the material that is highly explored by NET, one of them is through the ’JATANRAS’ (Crime and Violence) program. This study intends to discuss the forms of commodification that occur in the JATANRAS program. The research methodology used is qualitative, with a political economy approach that is in the realm of critical tradition. Data was collected through interviews with ’JATANRAS’ Producers. The results showed that there was a commodification process in the JATANRAS program, namely the commodification of content, the commodification of audiences, and the commodification of media workers. This research also shows that this program has characteristics as teletabloids where dramatization of police actions and criminal acts is made as the main commodity